Assessing distinguishable social skills in medical admission: does construct-driven development solve validity issues of situational judgment tests? - Mielke, Ina; Breil, Simon M.; Amelung, Dorothee; Espe, Lia; Knorr, Mirjana (BMC medical education, 2022)
Social skills are important for future physicians and are therefore increasingly considered in selection processes. One economic assessment method from which different social skills can be inferred are Situational Judgment Tests (SJTs) in which applicants are asked to rate behavioral responses in context-relevant situations. However, traditional SJTs have so far failed to distinctively measure specified constructs. To address this shortcoming in the medical admission context, we applied a construct-driven approach of SJT development in which test development was deductively guided by agency and communion as target constructs.